Sheath Tip Radial Artery Disruption as a Mechanism for Forearm Hematoma: Insights from the Distal Radial Artery Approach - Olaru Magda-Madalina; Lim Pitt O (Sciendo, 2024)
Radial artery occlusion (RAO), Forearm Hematoma (FH), and compartmental syndrome are three well-recognized complications associated with radial artery (RA) access to percutaneous coronary intervention (PCI). There are disparate ways the RA can be damaged, from multiple needling attempts to adverse interactions between the radial sheath, exchange wire, and diagnostic or guiding catheter with the artery.